Metody i narzędzia kształcenia zdalnego w polskich uczelniach w czasie pandemii COVID-19 – Część 2, Dyskusja 2020 - Topol, Paweł (Studia Edukacyjne, 2020)
The coronavirus disease forced a completely new situation in Polish education. All, or nearly all traditional forms of teaching and learning had to be transformed into remote and virtual ones. In the first half of this year (2020), an extensive discussion at the SEA Forum (the Academic E-learning Association) took place. Scientists and educators from various academic centers spoke about the methods and tools implemented in their institutions. Besides, another topic was launched on the SEA Forum simultaneously, devoted to possible recommendations regarding the planning and handling of e-learning methods, strategies and tools by Polish universities. This article is a certain synthesis of that discussion, i.e. how selected Polish universities, or rather their experts, perceive the next steps to make the distant teaching and learning process more successful and easier to handle by educators and students. The article is based on selected fragments and quotes of the debate. Many of them are commented on shortly by the author.